THE EFFECT OF RETURN ON INVESTMENT AND EARNINGS PER SHARE ON COMPANY STOCK PRICES WITH PERCEIVED RISK OF STOCKS AS MODERATING VARIABLES - Husniyah Husniyah; Tenriwaru Tenriwaru; Muh. Reza Ramdani (Contemporary Journal on Business and Accounting, 2021)
Purpose – This study aims to determine the effect of Return On Investment and Earning Per Share on Stock Prices with Perceived Risk of stocks as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Design/methodology/approach – The data analysis technique used is multiple linear regression analysis and Moderated Regression Analysis (MRA). Findings – The result of this study indicate that Return On Investment (ROI) has a negative and insignificant effect on stock prices of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Earning Per Share (EPS) has a positive and significant influence on stock prices of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Perceived Risk of shares has no effect on the relationship of ROI to stock prices of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Perceived Risk of shares has no effect on the relationship between EPS and stock prices of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Originality – This type of research is a quantitative research using secondary data in the form of annual reports of 10 sample companies taken from the website www.idx.co.id for the 2018-2020 period. Keywords: Earning Per Share (EPS), Perceived Risk of Stock, Return On Investment (ROI), Stock Price Paper Type Research Result